Sarkasme sebagai Bentuk Kritik Publik di Tiktok terhadap Film Animasi One For All: Merah Putih - Robi’ah Al Adawiyah; Fera Indasari; Muslimin Ritonga (Institut Nalanda, 2026)
The rapid growth of social media has transformed public communication into a more open and participatory digital space, particularly in expressing criticism toward cultural products through TikTok. One prominent phenomenon is the use of sarcasm in user comments on the animated film One For All: Merah Putih. This study aims to identify the forms and meanings of sarcasm as a strategy of public criticism in digital spaces. The research employs a qualitative approach using critical discourse analysis based on Teun A. van Dijk’s model. Data were collected from user comments on three TikTok videos posted by both media and personal accounts, and analyzed through the dimensions of text structure, social cognition, and social context. The findings reveal that sarcasm is the dominant form of expression in conveying criticism, manifested through irony, exaggerative expressions, and indirect insinuation. The novelty of this study lies in demonstrating that sarcasm functions not only as a linguistic style but also as a mechanism of public evaluation that reflects audience expectations and quality standards toward national animated films. These findings indicate that social media serves as an active discursive space in shaping public perception and opinion dynamics in the digital era.